Before the nation Muslim-Christian coexistence and its destruction in late Ottoman Anatolia - Doumanis, Nicholas (Oxford Oxford University Press, 2013)
"It is common for survivors of ethnic cleansing and even genocide to speak nostalgically about earlier times of intercommunal harmony and brotherhood. After being driven from their Anatolian homelands, Greek Orthodox refugees insisted that they 'lived well with the Turks', and yearned for the days when they worked and drank coffee together, participated in each other's festivals, and even prayed to the same saints. Historians have never showed serious regard to these memories, given the refugees had fled from horrific 'ethnic' violence that appeared to reflect deep-seated and pre-existing animosities. Refugee nostalgia seemed pure fantasy; perhaps contrived to lessen the pain and humiliations of displacement. Before the Nation argues that there is more than a grain of truth to these nostalgic traditions. It points to the fact that intercommunality, a mode of everyday living based on the accommodation of cultural difference, was a normal and stabilizing feature of multi-ethnic societies. Refugee memory and other ethnographic sources provide ample illustration of the beliefs and practices associated with intercommunal living, which local Muslims and Christian communities likened to a common moral environment. Drawing largely from an oral archive containing interviews with over 5000 refugees, Nicholas Doumanis examines the mentalities, cosmologies, and value systems as they relate to cultures of coexistence. He furthermore rejects the commonplace assumption that the empire was destroyed by intercommunal hatreds. Doumanis emphasizes the role of state-perpetrated political violence which aimed to create ethnically homogenous spaces, and which went some way in transforming these Anatolians into Greeks and Turks."--Publisher's website.
Curse of Babel -- Ottoman belle epoque -- People of God I -- People of God II -- Catastrophes.
Keywords: Christianity and other religions -- Islam -- History; Islam -- Relations -- Christianity -- History; Greeks -- History. -- Turkey; Turkey -- Ethnic relations -- History; Turkey -- History -- Ottoman Empire, 1288-1918.; Turkey -- Social conditions -- 1288-1918.